2020
DOI: 10.1093/jxb/eraa525
|View full text |Cite
|
Sign up to set email alerts
|

ABI5 regulates ABA-induced anthocyanin biosynthesis by modulating the MYB1-bHLH3 complex in apple

Abstract: Abscisic acid (ABA) induces anthocyanin biosynthesis in many plant species. However, the molecular mechanism of ABA-regulated anthocyanin biosynthesis remains unclear. As a crucial regulator of ABA signaling, ABSCISIC ACID-INSENSITIVE5 (ABI5) is involved in many aspects of plant growth and development. Nevertheless, whether ABI5 regulates anthocyanin biosynthesis has not been reported. In this study, we found that MdABI5, the homolog of Arabidopsis ABI5, positively regulated ABA-induced anthocyanin biosynthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 64 publications
1
52
0
Order By: Relevance
“…Arakawa et al [26] reported that a rapid increase in anthocyanin synthesis occurred in detached apples after 24 h of light exposure. Further, higher light intensity was reported to induce higher anthocyanin biosynthesis in apples [28]. Although the results of postharvest qualities revealed no significant damages (Table 1) following treatment with a UV-B intensity of 2.1 W•m −2 •S −1 , determining an appropriate light intensity and the duration of irradiation to achieve certain levels of red pigmentation is still required.…”
Section: Accumulation Of Idaein In Two Apple Maturity Stages Owing To...mentioning
confidence: 98%
“…Arakawa et al [26] reported that a rapid increase in anthocyanin synthesis occurred in detached apples after 24 h of light exposure. Further, higher light intensity was reported to induce higher anthocyanin biosynthesis in apples [28]. Although the results of postharvest qualities revealed no significant damages (Table 1) following treatment with a UV-B intensity of 2.1 W•m −2 •S −1 , determining an appropriate light intensity and the duration of irradiation to achieve certain levels of red pigmentation is still required.…”
Section: Accumulation Of Idaein In Two Apple Maturity Stages Owing To...mentioning
confidence: 98%
“…Abscisic acid (ABA), which is synthesized by the key cleavage enzyme 9‐ cis ‐epoxycarotenoid dioxygenase (NCED) in apocarotenoid pathway, has been shown to be a major regulator of ripening in non‐climacteric fruits, such as strawberry, grapes and bilberry (Ferrara et al, 2015; Jia et al, 2011; Karppinen, Tegelberg, Häggman, & Jaakola, 2018) and in climacteric fruits, such as apple (An et al, 2021). The ABA signal transduction is known to be mediated by pyrabactin resistance/like (PYR/PYL) receptors and ABA‐responsive element‐binding factors (ABFs) through SQUAMOSA‐MADS box (TDR‐type) TFs leading to regulation of the MBW complex proteins (Chung et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The bHLH proteins form one of the largest transcription factor families in plants. The anthocyanin biosynthesis-related SGIIIf bHLH genes have been identified in horticultural crops, including those encoding bHLH3 and bHLH64 transcription factors in apple and pear 58 , 59 . The R2R3-MYB transcription factor genes SlAN2-like and BrPAP1a encode regulators of anthocyanin production in tomato and turnip 60 , 61 .…”
Section: Discussionmentioning
confidence: 99%